Die dood van die outeur en die inspirasie van die Bybel: in gesprek met P.J. Nel en S.D. Snyman - P. Verster (In die Skriflig, 2005)
The death of the author and the inspiration of the Bible: in discussion with P.J. Nel and S.D. Snyman In the present debate on post-modernism, the question is also asked whether author’s intention can be indicated in a specific text. Nel (2003) and Snyman (2003) refer to this debate. Nel questions the view that author’s intention can be indicated in the Bible as text and especially doubts whether the view that God can be called the primary author of the Bible is still acceptable. Snyman suggests that present theories of inspiration should be expanded, since the history of the Bible’s origin is not adequately addressed in these theories. The concept of author’s intention should, however, not necessarily be disregarded, and the organic (personal) inspiration theory still offers the opportunity to explain the multifaceted aspects of the Bible. Presuppositions, however, play an important role in the views taken.